L-glutaminase synthesis by Klebsiella pneumoniae (AS KP 23) isolated from clinical strain, and its efficacy against human hepatocellular and breast cancer cell lines - Lina J. Abdel-Hafez; Eman Y. T. Elariny; Asmaa E. Ibrahim; Mahmoud E. F. Abdel-Haliem (BMC Microbiology)
Abstract Background Cancer is a major cause of morbidity and mortality worldwide. The proliferation of cancer cells depends largely on glutamine for survival and proliferation. Glutamine serves as a carbon source for the synthesis of metabolites and lipids via the TCA cycle, as well as a source of nitrogen for the synthesis of amino acids and nucleotides. Recently, the role of glutamine metabolism in cancer has been explored in many studies. Therefore, it provides a scientific relationship for targeting glutamine metabolism for cancer treatment. L-glutaminase which is a powerful anticancer medication that is widely used around the world, works by removing L-glutamine from cancerous cells. L-glutaminase has been cited as the most potent molecule that inhibits the proliferation of cancer cells, which significantly raises the possible applicability of cancer therapy and the possibility of its application as an alternative drug to chemotherapy. The first investigation into the antitumor property of L-glutaminase revealed its inhibitory effect on the growth of Gardner lymphosarcoma (6C3HED) and L-1210 leukemia cells. In the same study, glutaminase from Pseudomonas spp., in combination with azaserine enhanced the degree of tumor growth inhibition. Subsequently, L-glutaminase was administered intravenously in patients with acute lymphoblastic leukemia and acute myeloid leukemia. Recently, a purified L-glutaminase from Streptomyces sp. D214 was shown to be the most effective, with an IC50 value of 10 mg/ml against the MCF-7 tumor cell line. Also, various in vitro studies have revealed that the activity of glutaminase against the proliferation of tumor cell lines using the MTT (3-(4,5- dimethylthiazol-2-yl)- 2, 5-diphenyltetrazolium bromide) cell proliferation assay. Alcaligenes faecalis KLU102 glutaminase was able to reduce the viability of HeLa cells in a dose-dependent manner, with an IC50 value of 12.5 mg/ml within 24 h. Results In this study, a bacterium extracellular from human stool samples was extracted and identified using morphological, biochemical, and molecular methods. The 16 S rRNA gene was 100% identical to the sequence from Klebsiella pneumoniae and was submitted to GenBank under accession number OQ703039. Thus, this strain was named Klebsiella pneumoniae AS KP 23. Further kinetic studies on the purified enzyme were performed. In addition, the pH stability of the L-glutaminase enzyme was slightly affected over the pH range of 7.0–9.0 after 2 h of pre-incubation, and the rate of thermal inactivation of the L-glutaminase enzyme increased with higher temperatures and longer preheating periods. In addition, the stability of the tested enzyme decreased with an increasing storage period at -20 °C. The SDS-PAGE revealed that the L-glutaminase subunits had a molecular weight of around 97 kDa. L-glutaminase was purified 1.33-fold with a final specific activity of 799.9 U/mg protein using gel filtration chromatography. The enzyme´s cytotoxic activity showed severe toxicity against the HepG-2 human hepatocellular and breast cancer cell lines. Klebsiella pneumoniae glutaminase was able to reduce the viability of HeLa cells in a dose-dependent manner, with an IC50 value of 305.78 µg/ml in human hepatocellular carcinoma and an IC50 value of 400.51 µg/ml in breast cancer cell lines. Conclusion Klebsiella pneumoniae AS KP 23 was a genetically determined microbial species isolated from human stool samples. The production of extracellular enzymes was examined. Additionally, purified L-glutaminase inhibited the growth of normal cells and showed potent anticancer activity against numerous cancer cell lines in the study. Its broad pH and temperature range, combined with its unique and highly stable catalytic activity, make it an excellent choice for use as an effective cancer inhibitor.